Analisis dan Implementasi Sistem Peminjaman Ruangan berbasis Google Workspace Studi Kasus STT Terpadu Nurul Fikri - Dwi Sundari, Ayu; Rahmah, Amalia (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
The room loan application service is one of the academic services the Nurul Fikri Integrated Technology College provides. The room loan application service at the Nurul Fikri Integrated Technology College is still done manually, where the Student Affairs Staff manages the physical room loan application service, and the Study Program staff works the virtual room loan application service. Problems include loan data not being archived properly, conflicting loan applications, and the process being quite long. This research aims to create a Google Sheet-based Google Form and Dashboard that facilitates the application process and management of room loans at the Nurul Fikri Integrated Technology College. The research method used in this study is the mixed method research method, which combines qualitative and quantitative research. The test results of the implementation of the use of Google Forms and Dashboards based on Google Sheets for Room Loans are 100% for students, 100% for students, and 100% for Study Program staff, which means that the existence of Google Forms and Dashboards based on Google Sheets for Room Loans makes it easier for students to apply for loans. Physical and virtual rooms, as well as facilitate data management of physical room loan applications for Student Staff and simplify data management of virtual room loan applications for Study Program staff.